Synthetic 3D diamond-based electrodes for flexible retinal neuroprostheses: Model, production and in vivo biocompatibility. (October 2015) - Bendali, Amel; Rousseau, Lionel; Lissorgues, Gaëlle; Scorsone, Emmanuel; Djilas, Milan; Dégardin, Julie; Dubus, Elisabeth; Fouquet, Stéphane; Benosman, Ryad; Bergonzo, Philippe; Sahel, José-Alain; Picaud, Serge
Abstract: Two retinal implants have recently received the CE mark and one has obtained FDA approval for the restoration of useful vision in blind patients. Since the spatial resolution of current vision prostheses is not sufficient for most patients to detect faces or perform activities of daily living, more electrodes with less crosstalk are needed to transfer complex images to the retina. In this study, we modelled planar and three-dimensional (3D) implants with a distant ground or a ground grid, to demonstrate greater spatial resolution with 3D structures. Using such flexible 3D implant prototypes, we showed that the degenerated retina could mould itself to the inside of the wells, thereby isolating bipolar neurons for specific, independent stimulation. To investigate the in vivo biocompatibility of diamond as an electrode or an isolating material, we developed a procedure for depositing diamond onto flexible 3D retinal implants. Taking polyimide 3D implants as a reference, we compared the number of neurones integrating the 3D diamond structures and their ratio to the numbers of all cells, including glial cells. Bipolar neurones were increased whereas there was no increase even a decrease in the total cell number. SEM examinations of implants confirmed the stability of the diamond after its implantation in vivo . This study further demonstrates the potential of 3D designs for increasing the resolution of retinal implants and validates the safety of diamond materials for retinal implants and neuroprostheses in general.